Transgenic Insects Techniques and Applications (2nd edition) - Benedict, Mark Quentin; Scott, Maxwell J (CABI, 2022)
Technology for modifying the genotypes and phenotypes of insects and other arthropods has steadily progressed with the development of more precise and powerful methods, most prominently transgenic modification. For many insect pests, there is now almost unlimited ability to modify phenotypes to benefit human health and agriculture. Precise DNA modifications and gene drive have the power to make wild-type populations less harmful in ways that could never have been performed with previous transgenic approaches. This transition from primarily laboratory science to greater application for field use has also necessitated greater development of modeling, ethical considerations and regulatory oversight. The 2nd Edition of Transgenic Insects contains chapters contributed by experts in the field that cover technologies and applications that are now possible. This edition includes increased attention to associated challenges of risk assessment, regulation, and public engagement. Featuring: Up-to-date analysis of molecular techniques, such as gene editing. Consideration of public attitudes and regulatory aspects associated with transgenic insects. Many examples of the wide range of applications of transgenic insects. This book will be very valuable to students and researchers in entomology, molecular biology, genetics, public health and agriculture, and will also appeal to practitioners who are implementing the technology, and to regulators, stakeholders and ethicists.